1991
DOI: 10.1128/mcb.11.5.2460
|View full text |Cite
|
Sign up to set email alerts
|

An A + U-rich element RNA-binding factor regulates c-myc mRNA stability in vitro.

Abstract: Transient expression of some proto-oncogenes, cytokines, and transcription factors occurs as a cellular response to growth factors, 12-O-tetradecanoylphorbol-13-acetate, antigen stimulation, or inflammation. Expression of these genes is mediated in part by the rapid turnover of their mRNAs. A+U-rich elements in the 3' untranslated regions of these mRNAs serve as one recognition signal targeting the mRNAs for rapid degradation. I report the identification of a cytosolic factor that both binds to the proto-oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
356
2
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(377 citation statements)
references
References 49 publications
18
356
2
1
Order By: Relevance
“…As shown in Figure 2a, a few short sequences that are signi®cantly homologous to reported cis-repressive elements could be found in the 200 bp area (Brewer, 1991;Sterling and Bresnick, 1996;Ogbourne and Antalis, 1998). Assuming that these putative elements might be involved in the observed repressive e ect, two deletion mutants of SA3 were prepared.…”
Section: Identification Of a Minimal Cis-acting Repressive Element Inmentioning
confidence: 90%
“…As shown in Figure 2a, a few short sequences that are signi®cantly homologous to reported cis-repressive elements could be found in the 200 bp area (Brewer, 1991;Sterling and Bresnick, 1996;Ogbourne and Antalis, 1998). Assuming that these putative elements might be involved in the observed repressive e ect, two deletion mutants of SA3 were prepared.…”
Section: Identification Of a Minimal Cis-acting Repressive Element Inmentioning
confidence: 90%
“…In contrast with ABIN-1 and A20, ABIN-2 mRNA expression is not modulated upon stimulation of cells with TNF, LPS or interferon- [29], and is therefore believed to be NF-B independent However, ABIN-2 mRNA expression is augmented in adult mouse liver after partial hepatectomy, and like A20, in progesterone-stimulated progesterone receptor B expressing cells [32,33]. Furthermore, the 3'-untranslated region of ABIN-2 mRNA contains two binding sequences for 'AU-rich element binding factor 1' (AUF1), which has been suggested to regulate mRNA turnover [34]. In the case of rat uterus ABIN-2 mRNA, these sequences were indeed shown to bind AUF1, and ABIN-2 mRNA was 9 upregulated with the same kinetics as cytoplasmic AUF1 protein isoforms in ovariectomized rat uteri stimulated with 17-estradiol [35].…”
Section: Abin-2mentioning
confidence: 99%
“…More recent studies have identified other factors capable of binding AREs with various degrees of avidity. These include selected nuclear ribonucleic proteins (hnRNP A1, hnRNP C (Hamilton et al, 1993), hnRNP D, also known as AUF-1 (Brewer, 1991)), RNA-binding proteins displaying enzymatic activities (GAPDH (Nagy and Rigby, 1995), AUH (Nakagawa et al, 1995)), other HuR-like proteins, belonging to the ELAV family (embryonic lethal abnormal vision) and related to the Drosophila neuron-specific RNA-binding proteins (Hel-N1, HuC, HuD, (Levine et al, 1993;Good, 1995;Ma et al, 1996) and HuR (Fan and Steitz, 1998;Peng et al, 1998), heat shock protein 70 (Hsp70) and others (AUBP (Malter and Hong, 1991), AU-A, AU-B, AU-C (Bohjanen et al, 1991(Bohjanen et al, , 1992, tristetraprolin (Taylor et al, 1996b), butyrate response factor-1 (BRF1), encoding a zinc finger protein homologous to tristetraprolin (Stoecklin et al, 2002), KSRP ), TIA-1 and TIAR (Piecyk et al, 2000)). …”
Section: Are Binding Factorsmentioning
confidence: 99%
“…Normally, the p42 and p45 isoforms appear exclusively in the nucleus (Zhang et al, 1993;Arao et al, 2000). P37 AUF1 and/or p40 AUF1 are associated with the acceleration of mRNA turnover by ARE: a protein complex containing cytoplasmic p37 AUF1 and p40 AUF1 is able to destabilize polysomal c-myc mRNA in vitro (Brewer, 1991). The affinity of recombinant p37 AUF1 for the ARE motif is closely correlated with its potential to destabilize the mRNA .…”
Section: Auf1mentioning
confidence: 99%